COVID-19 and E-commerce - United Nations Conference on Trade; Development (United Nations, 2021)
Since the outbreak of the new coronavirus disease (COVID-19) pandemic, UNCTAD has played a critical role in raising awareness on the opportunities emerging from the crisis through increasing the uptake of e-commerce and digital solutions. At the same time, UNCTAD has voiced concerns about the risk of rising digital inequalities, particularly in least developed countries (LDCs). The 2020 eCommerce Week organised virtually by UNCTAD and partners of the eTrade for all initiative provided a unique platform convening a wide range of stakeholders to assess implications of the crisis and explore in-depth key digital issues in the context of the COVID-19 pandemic. As a follow-up, UNCTAD assessed the impact on e-commerce businesses across developing countries and LDCs to understand the magnitude of the impact, identify key trends and challenges faced by e-commerce businesses, as well public and private policy responses to cope with the crisis. This paper is based on the results of a survey that investigates the impact of COVID-19 on e-commerce businesses from early March to the end of July 2020. It focuses on 23 countries, mainly LDCs, in Africa and Asia-Pacific. The countries have all benefitted from UNCTAD’s e-commerce capacity building programmes, either through an eTrade Readiness Assessment (eT Ready) or a national e-commerce strategy. 257 representatives of e-commerce businesses, out of 699 invited, responded to the survey and shared their experience following the outbreak of the COVID-19 pandemic. Businesses have been divided into two groups: companies selling at least parts of their goods or services online and third-party online marketplaces. The responses from the private sector were complemented by public sector responses from 12 countries, elaborating on measures taken during the COVID-19 crisis to support e-commerce as well as to use e-commerce for economic recovery efforts. The key findings of this paper are presented below.